Modelling antennas in outer space using the boundary element unstructured transmission-line (BEUT) method - Simmons, Daniel; Cools, Kristof; Sewell, Phillip (2015)
In this paper the hybridization of the 2D time domain boundary element method (BEM) with the unstructured transmission line method (UTLM) is described. The novel method enables accurate modelling of radiating boundary conditions, excitation by plane waves, and efficient modelling of problems containing large free-space regions and non-uniform materials. The method has been developed to more accurately describe arbitrary surfaces and is demonstrated by comparing numerical results against analytical results.